Ground station and offboard control of a hexarotor unmanned aerial vehicle - Teo, Winnie (2016)
The use of UAVs has increased dramatically around the world due to increase access to this technology and affordable in the case of civilian UAVs. Although the technology of military and civilian UAVs have increased tremendously but the need of ground station cannot be eliminated as it is pretty risky to let UAVs to control on its own without someone monitoring it as crashes can occurred quite frequently due to pilot error or hardware or software malfunction. The ground control station can consolidate the real time flight data together and display it into a form of the normal pilot cockpit display and map display on the screen. Mission plans can be pre-loaded into the UAVs while the operator can just monitor the UAVs by moving map display to ensure every things went smoothly. Therefore the objective of this project is to implement a ground station for hexarotor, a six motors rotor and at the same time to implement codes to allow hexarotor to perform flight mission using an offboard command.